1991
DOI: 10.1055/s-2007-999371
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcome Following First Trimester Exposure to Chloroquine

Abstract: Although the use of chloroquine (C) and hydroxychloroquine (HC) in the treatment of malaria prophylaxis during pregnancy is probably safe, the use of much higher doses for treatment of systemic lupus erythematosus (SLE) and rheumatoid arthritis during pregnancy has been controversial. We analyzed the cases of 24 pregnant women with a total of 27 pregnancies who had taken these drugs during their first trimester of pregnancy. C and HC were given in 11 patients with SLE, three with rheumatoid arthritis, and four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
4

Year Published

1997
1997
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(62 citation statements)
references
References 10 publications
0
58
0
4
Order By: Relevance
“…[41] In a review of 215 reported pregnancies with chloroquine or hydroxychloroquine exposure, only seven (3.3%) had congenital abnormalities. [42] In multiple centers dealing with lupus pregnancy, including our own, no congenital abnormalities have been found with hydroxychloroquine use. [36,43,44] Follow-up of children exposed in utero has not detected any abnormalities in vision or hearing, [36] including a prospective clinical trial.…”
Section: Placental Transfermentioning
confidence: 83%
“…[41] In a review of 215 reported pregnancies with chloroquine or hydroxychloroquine exposure, only seven (3.3%) had congenital abnormalities. [42] In multiple centers dealing with lupus pregnancy, including our own, no congenital abnormalities have been found with hydroxychloroquine use. [36,43,44] Follow-up of children exposed in utero has not detected any abnormalities in vision or hearing, [36] including a prospective clinical trial.…”
Section: Placental Transfermentioning
confidence: 83%
“…Chloroquine, a 4-aminoquinoline, is a weak base that is rapidly imported into acidic vesicles, increasing their pH [46,47]. It is approved by the FDA to treat malaria and has long been prescribed prophylactically to pregnant women that are at risk of exposure to Plasmodium parasites [48,49]. Both chloroquine and the related compound, hydroxychloroquine, are used in the treatment of systemic lupus erythematous and rheumatoid arthritis due to their anti-inflammatory properties [50].…”
Section: Chloroquinementioning
confidence: 99%
“…Para el tratamiento de la artritis asociada a ES durante el embarazo, pueden utilizarse analgésicos como paracetamol, dosis bajas de corticoides (menos de 15 mg/día de prednisona o su equivalente), hidroxicloroquina o, a falta de esta, cloroquina, a las dosis y temporadas mínimas necesarias, ya que no se han asociado a un incremento en la tasa de defectos congénitos ni a complicaciones de la esclerodermia 20,67,68 . Los antiinflamatorios no esteroideos deben limitarse por su asociación con oligohidramnios.…”
Section: Plan De Manejounclassified